Transformation of Contemporary Fiqh through a Collective Ijtihad Approach in Resolving Lineage Issues Arising from Egg Freezing - Edi Susilo; Budi Santoso; Yessy Eka Ambarwati (Faculty of Sharia, IAIN Metro, 2025)
Egg freezing has triggered scholarly debate in Islamic jurisprudence, particularly when eggs are frozen before marriage and used afterward, raising concerns about the child's lineage. Contemporary fiqh through collective ijtihad is needed to offer solutions aligned with maqasid al-shariah. This research aims to analyze the formulation of contemporary fiqh in determining the legal ruling on egg freezing through a collective ijtihad framework. The study adopts a qualitative approach with a normative-empirical method. Data were collected through a literature review of classical fiqh texts, academic journals, and scholarly fatwas, followed by a descriptive-qualitative analysis. The findings of this study indicate that the formulation of contemporary Islamic jurisprudence through the collective ijtihad approach serves as an effective method for resolving lineage-related issues arising from egg freezing. The first step in the collective ijtihad process involves considering input from medical experts, beginning with a detailed presentation of the procedures, including ovarian stimulation, followed by the retrieval of mature oocytes, which are then cryopreserved using vitrification techniques to ensure optimal quality for long-term storage. Subsequently, Islamic jurists analyze and deliberate on the issue from various jurisprudential perspectives. Egg freezing is considered permissible as long as it is conducted within the framework of lawful marriage and upholds the principle of hifz al-nasl (protection of lineage). This study contributes to the advancement of Islamic legal thought that is responsive to the developments in reproductive technologies.